An Introduction to the q-Laguerre-Hahn Orthogonal q-Polynomials - Ghressi, A.; Khériji, L.; Tounsi, M.I. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
Orthogonal q-polynomials associated with q-Laguerre-Hahn form will be studied as a generalization of the q-semiclassical forms via a suitable q-difference equation. The concept of class and a criterion to determinate it will be given. The q-Riccati equation satisfied by the corresponding formal Stieltjes series is obtained. Also, the structure relation is established. Some illustrative examples are highlighted.